REFLEKSI KRISIS SOSIAL GLOBAL DALAM PENGEMBANGAN KARAKTER ANAK USIA SEKOLAH DASAR: PENDEKATAN HUMANISTIK-KONTEKSTUAL - Muamar; Ilman Nafi’a (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid global social transformation has posed serious challenges to character education at the elementary school level. Young children today are growing up in a complex value landscape shaped by technological disruption, social solidarity crises, and widespread cultural shifts. This study aims to examine how the global social crisis is reflected in the dynamics of character education for elementary students and to explore humanistic and contextual approaches as responsive strategies. This qualitative research employed data collection techniques including observation, in-depth interviews, and document analysis in two elementary schools in Brebes Regency, Indonesia. The findings reveal that children face value tensions stemming from social media and globalized environments, affecting their empathy, behavior, and moral identity. Teachers and schools tend to implement character education in a normative and fragmented manner, often disconnected from students' real-life contexts. The study highlights that a humanistic approach centering learners as subjects—and a contextual approach connecting values with lived experiences are more effective in fostering authentic character development. This research contributes a new perspective to the study of character education in the age of global disruption by proposing an integrated pedagogical strategy grounded in humanization and social relevance. The implications call for a reformulation of policies and practices in elementary character education to ensure greater adaptability to the social crises that increasingly impact children from an early age.